Implementasi Pendidikan SpiritualDi Sekolah Menengah Kejuruan Muhammadiyah 2Cepu Blora Tahun 2015 - RAKHMANTO, NUR FATONI HADI (2016)
ABSTRACT This research intent to describe educational critical about spiritual education in curriculum implementation at SMK Muhammadiyah 2 Cepu Blora and in order to look for answers about problems about how spiritual's educations in formal curriculum implementation and spiritual's education in hidden curriculum, and to know supporting factor and education resistor factor spiritual in curriculum implementation at SMK Muhammadiyah 2 Cepu Blora. This observational type constitute field research with observational object at SMK Muhammadiyah 2 Blora's Caskets. There is character even this research is descriptive qualitative who gets effort to give pictures that details about background, character and typical character of aught case at the site. To explore data did by intensive relationship with data source. Data as description hit activity or subject behaviour and acquired other documents through interviews, observation and documentation. Result observationaling to point out that curriculum implementation at SMK Muhammadiyah 2 Cepu Blora was performed according to steps, approaching, and principles and basis for operational already being established by BSNP. In curriculum implementation exists spiritual's education that covers is ardour accountability, discipline, obedience, sincerity, independence, affection, convenience, goodwill, familiarity, example, conspectus, harmonious life and communicative, creative, deliberation, motivation, security, orderliness, consciousness to power Khaliq, attitude respects, seriousness, politeness, and tawakals attitude. Spirituals education in implementation hidden curriculum covering discipline, obedience, orderliness, accountability, chastity self, togetherness, tolerance, sincerity, good being, hygiene, aesthetical, convenience, patient, elegance, decency, social, respect, affection. That attitude constitute realizations of spiritual's dimension root namely godfearing, khusyu', tawadhu ', khauf, raja', muraqabah, istiqamah. Educations supporting factor spiritual in curriculum implementation which is be accomplished curriculum component, learning media, yen and student spirit, educator and energy to education that accomplishes qualification academic and also religiousity, environmentally which conditional. Its resistor factor for example reducing it supporter book at bibliographic; was accomplished its about building medium comprehensif; mark sense severally instructor energy that mismatch ; religiousity ability student, mark sense learning strategy elect that insufficiently accords, infrastructure medium laboratory also being felt still haven't stándar in comparison with student amount at SMK Muhammadiyah 2 Cepu Blora. Keywords : spiritual education, implementation, curriculum